Comparative pharmacokinetic analysis of raw and steamed Panax notoginseng roots in rats by UPLC-MS/MS for simultaneously quantifying seven saponins. (1st January 2021) - Dong, Jiajia; Yin, Zhenzhen; Su, Lianlin; Yu, Mengting; Wang, Meng; Li, Lin; Mao, Chunqin; Lu, Tulin
Abstract: Context: After being steamed, the restorative effects of Panax notoginseng (Burk.) F. H. Chen (Araliaceae) will be strengthened. However, the underlying mechanism remains elusive. Objective: To compare the pharmacokinetics of ginsenosides Rg1, Rb1, Rd, Re, Rg5, Rk1, notoginsenoside R1 (GRg1, GRb1, GRd, GRe, GRg5, GRk1 and NGR1 ) in the raw and steam-processed P. notoginseng (RPN and SPN). Materials and methods: The pharmacokinetics of seven components after oral administration of SPN and RPN extracts (1.0 g/kg) were investigated, respectively, in SD rats (two groups, n = 6) using UPLC-MS/MS. Results: The approach elicited good linear regression ( r 2 > 0.991). The accuracy, precision and stability were all within ± 15%. The extraction recoveries and matrix effects were 75.0–100.8% and 85.1–110.3%, respectively. Compared with the RPN group, AUC0– t of GRg1 (176.63 ± 42.49 ng/h/mL), GRb1 (5094.06 ± 1453.14 ng/h/mL), GRd (1396.89 ± 595.14 ng/h/mL), and NGR1 (135.95 ± 54.32 ng/h/mL), along with C max of GRg1 (17.41 ± 5.43 ng/mL), GRb1 (361.48 ± 165.57 ng/mL), GRd (62.47 ± 33.65 ng/mL) and NGR1 (23.97 ± 16.77 ng/mL) decreased remarkably with oral administration of the SPN extracts, while GRe showed no significantly difference. Of note, GRg5 and GRk1 could not be detected in the plasma. Conclusions: Influence of the processing reduced the systemic exposure levels to GRg1, GRb1, GRd and NGR1 . It is the first report of comparative pharmacokinetic study of multiple saponins analysis after oral administration of RPN and SPN extract, which might be helpful for further studies on its steam-processing mechanism.